(untitled) (American Journal of Technology and Applied Sciences, 2025)
The kinetics of anodic dissolutions of gold-silver alloys containing up to 20 wt. % silver in hydrochloric acid solutions of varying concentrations was investigated using the electrochemical method of polarization curves. It was demonstrated that the dependence of current on time can be consistently described by models of the formation and thickening of a porous silver chloride film, taking into account the partial current of silver and its dependence on the alloy composition.